2016
DOI: 10.1017/s0033291716002877
|View full text |Cite
|
Sign up to set email alerts
|

Educational achievement in psychiatric patients and their siblings: a register-based study in 30 000 individuals in The Netherlands

Abstract: Educational underachievement from primary school onwards is specifically related to schizophrenia and not to bipolar disorder or depression. Moreover, it appears to be a harbinger of the illness, since it is not found in their siblings. These results add to evidence that early cognitive deficits are a distinct feature of the schizophrenia phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 39 publications
4
29
1
Order By: Relevance
“…It is well established that indirect costs, such as non‐employment, constitute a large part of the total economic burden caused by mental disorders . Most previous studies have also shown that most disorders are associated with lower rates of employment and low income , but not necessarily with low education . To our knowledge, the current study is one of the largest to examine the associations of serious mental disorders with subsequent economic outcomes and the first one to compare the associations between different mental disorders that are critical for policy decisions to allocate the healthcare resources to the treatment of these conditions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is well established that indirect costs, such as non‐employment, constitute a large part of the total economic burden caused by mental disorders . Most previous studies have also shown that most disorders are associated with lower rates of employment and low income , but not necessarily with low education . To our knowledge, the current study is one of the largest to examine the associations of serious mental disorders with subsequent economic outcomes and the first one to compare the associations between different mental disorders that are critical for policy decisions to allocate the healthcare resources to the treatment of these conditions.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, studies that have examined the association between mental disorders with educational attainment have produced partially mixed findings. Whereas cross‐sectional and longitudinal survey studies have found that most mental disorders are associated with poor educational attainment , a recent register‐based study from the Netherlands founded that schizophrenia, but not depression or bipolar disorder, were associated with lower likelihood of obtaining secondary or higher education . Taken together, it seems that mental disorders can lead to irregular work careers and permanently low income, thus increasing the total economic burden of mental disorders .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is known that achievement is significantly lower in cognitively unselected schizophrenia patients than in the general population and relative to other psychiatric populations [36]. However, patients with normal range cognition are relatively rare and represent a special subgroup of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Economic evaluations have estimated that the total costs of mood disorders are enormous (Cloutier, Greene, Guerin, Touya, & Wu, ; Greenberg, Fournier, Sisitsky, Pike, & Kessler, ; Kessler et al, ; Luppa, Heinrich, Angermeyer, König, & Riedel‐Heller, ), with unemployment and other indirect costs typically being the largest components of the total economic costs (Cloutier et al, ; Greenberg et al, ). A number of prospective observational cohort studies have shown that mood disorders are associated with poor socioeconomic outcomes in terms of occupational status and income (Ahola et al, ; Hakulinen et al, ; Marwaha, Durrani, & Singh, ; Mojtabai, Stuart, Hwang, & Susukida et al, ; Whooley et al, ; Zimmerman & Katon, ); however the findings regarding mood disorders and subsequent educational attainment are mixed (Mojtabai, Stuart, Hwang, Eaton et al, ; Tempelaar, Termorshuizen, MacCabe, Boks, & Kahn, ).…”
Section: Introductionmentioning
confidence: 99%